13
$\begingroup$

I would like to know how to prove the following two definite integrals.

A: $$\int_{0}^1\frac{x-1}{\log x}dx=\log 2$$

B:$$\int_{0}^1\frac{\log x}{x-1}dx=\frac{\pi^2}{6}$$

I found these two by using wolfram-alpha, but I can't prove them. I suspect that the following relations might be used.

$$\log 2=1-\frac{1}{2}+\frac{1}{3}-\frac{1}{4}+\cdots=\sum_{n=1}^\infty\frac{(-1)^{n-1}}{n}$$and$$\frac{\pi^2}{6}=\frac{1}{1^2}+\frac{1}{2^2}+\frac{1}{3^2}+\frac{1}{4^2}+\cdots=\sum_{n=1}^\infty\frac{1}{n^2}$$

I need your help.

$\endgroup$
15
$\begingroup$

Consider $$f(p)= \int_0^1\frac{x^p-1}{\log x}dx$$

Then $$f'(p)=\int_0^1x^pdx=\frac{1}{p+1}$$

Then integrate.

For the other, use that $$\int_0^1x^{n}\log x=-\frac{1}{(n+1)^2}$$

and that $$\frac{1}{1-x}=\sum_{n\geqslant 1}x^n$$

$\endgroup$
  • $\begingroup$ Nice one on the Feynman trick. +1 $\endgroup$ – Fixed Point Aug 20 '13 at 7:47
7
$\begingroup$

For A

Consider the following

$$I(a)=\int^1_0 \frac{x^a-1}{\log(x)}\, dx$$

Differentiate w.r.t to $a$ to get

$$I'(a)=\int^1_0 x^a dx=\frac{1}{a+1}$$

Hence

$$I(a) = \log(a+1)+C$$

By $a=0$ we have $C=0$ Hence

$$I(a) = \log(a+1)$$

Hence $$I(1) = \int^1_0 \frac{x-1}{\log(x)}\, dx = \log(2)$$

For part B

We know that

$$\int^1_0 \frac{\log(x)}{x-1}\, dx=-\int^1_0 \frac{\log(1-x)}{x}\, dx=\operatorname{Li}_2(1)=\zeta(2)$$

This can be proven through the power expansion

$$-\int^1_0 \frac{\log(1-x)}{x}=\sum_{k\geq 1}\frac{1}{k^2}=\zeta(2)$$

$\endgroup$
4
$\begingroup$

\begin{eqnarray*} \int_{0}^{1}{x - 1 \over \ln\left(x\right)}\,{\rm d}x & = & \int_{0}^{\infty}{{\rm e}^{-x} - {\rm e}^{-2x} \over x}\,{\rm d}x = -\int_{0}^{\infty}\ln\left(x\right)\,\left(-{\rm e}^{-x} + 2{\rm e}^{-2x}\right)\,{\rm d}x \\ & = & \int_{0}^{\infty}\ln\left(x\right)\,{\rm e}^{-x}\,{\rm d}x - \int_{0}^{\infty}\ln\left(x \over 2\right)\,{\rm e}^{-x}\,{\rm d}x = \ln\left(2\right)\ \overbrace{\quad\int_{0}^{\infty}{\rm e}^{-x}\quad}^{1} = \ln\left(2\right) \\[1cm] &&\mbox{Or/and try this} \\ I\left(\mu\right) & \equiv & \int_{0}^{1}{x^{\mu} - 1 \over \ln\left(x\right)}\,{\rm d}x\,, \quad I'\left(\mu\right) = \int_{0}^{1}{x^{\mu}\ln\left(x\right) \over \ln\left(x\right)}\,{\rm d}x \\ I'\left(\mu\right) & = & \left.{x^{\mu + 1} \over \mu + 1}\right\vert_{0}^{1} = {1 \over \mu + 1} \quad\Longrightarrow\quad I\left(1\right) - I\left(0\right) = \int_{0}^{1}{{\rm d}\mu \over \mu + 1} = \ln\left(2\right) \end{eqnarray*}

\begin{eqnarray*} &&\\[1cm] \int_{0}^{1}{\ln\left(x\right) \over x - 1}\,{\rm d}x & = & \int_{0}^{\infty}x{\rm e}^{-x}\,{1 \over 1 - {\rm e}^{-x}}\,{\rm d}x = \int_{0}^{\infty}x{\rm e}^{-x}\,\sum_{n = 0}^{\infty}{\rm e}^{-nx}\,{\rm d}x = \sum_{n = 0}^{\infty} \int_{0}^{\infty}x\,{\rm e}^{-\left(n + 1\right)x}\,{\rm d}x \\ & = & \sum_{n = 0}^{\infty}{1 \over \left(n + 1\right)^{2}}\ \overbrace{\quad\int_{0}^{\infty}x\,{\rm e}^{-x}\,{\rm d}x\quad}^{1} = \sum_{n = 0}^{\infty}{1 \over \left(n + 1\right)^{2}} \\ & = & {\pi^{2} \over 6}\,,\quad\mbox{( Basel Problem )} \end{eqnarray*}

http://en.wikipedia.org/wiki/Basel_problem. See also: http://empslocal.ex.ac.uk/people/staff/rjchapma/etc/zeta2.pdf

$\endgroup$
  • $\begingroup$ Note your second equality is followed by a Frullani integral. $\endgroup$ – Pedro Tamaroff Oct 31 '13 at 22:12
  • $\begingroup$ @PedroTamaroff I didn't know that. Thanks to your comment I found some interesting $\tt .pdf$ about it: ( 129.81.170.14/~vhm/papers_html/final15.pdf ). Thanks. $\endgroup$ – Felix Marin Nov 2 '13 at 20:34
2
$\begingroup$

In what follows, we will use the Taylor series expansion for the natural logarithm: $$\quad\ln(1-x)\ =\ -\sum_{n=1}^\infty\frac{x^n}n\quad,\quad|x|\leqslant1,$$ coupled with the fact that the integral of a sum is the sum of integrals. $$\int_0^1\frac{\ln x}{x-1}dx\ =\ -\int_0^1\frac{\ln(1-x)}xdx\ =\ +\int_0^1\frac1x\cdot\sum_{n=1}^\infty\frac{x^n}ndx\ =\ \sum_{n=1}^\infty\int_0^1\frac{x^{n-1}}ndx=$$ $$=\ \sum_{n=1}^\infty\frac{x^n}{n^2}\Bigg|_{\ 0}^{\ 1}\ =\ \sum_{n=1}^\infty\frac1{n^2}\ =\ \zeta(2)\ =\ \frac{\pi^2}6.$$ As to why the sum in question equals $\frac{\pi^2}6$ , see Basel problem.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.